Group Accounting: The Effect of IFRS Adoption. The Case of Greece - Ioannis Samaras; Stergios Athianos (Journal of Accounting and Management Information Systems (JAMIS), 2016)
The present study examines the value relevance of disclosed related party transactions (RPTs) in the Greek listed companies on the Athens Stock Exchange. We are based on two types of transactions: exchange of goods-products and the exchange of assets (group accounting), using a value relevance approach. We apply the model of Ohlson (1995) for the period 2003 - 2013 and we observe that the reported earnings of firms selling goods or assets to related parties exhibit a lower valuation coefficient than those of firms without such transactions. The Greek accounting standards provide limited recognition of assets, together with the frequent use of forecasts, resulting in a more conservative recognition of results compared to the IAS / IFRS, which are using fair value for the recognition of financial instruments and internally generated intangible assets.
Keywords: M41; 650; IFRS; value relevance; group accounting; financial reporting